PROPOSED NEW PRODUCT DEVELOPMENT CONCEPT OF ELECTRIC VEHICLE BY USING CHOICE-BASED CONJOINT ANALYSIS (A CASE STUDY: PT. LIS) - Choerul Fatihin, Riva
Indonesian automotive industry has become a vital pillar of the country's manufacturing sector. Furthermore, as per capita GDP increased, Indonesia transitioned from a purely exportoriented vehicle production hub (particularly for the Southeast Asian region) to a large (domestic) car sales market. At the same time, increasing production and usage of vehicles considerably increases energy consumption and greenhouse gas emissions. Since 2012, the transportation sector, including automotive industry, has been the highest final energy consumer and passenger cars are a primary source of CO2 emissions in the road transportation sector. Developing electric vehicles is considered a possible solution to minimize greenhouse gas emissions, improve air quality, and reduce reliance on oil. Indonesia plans to shift to the electric vehicle era following Presidential Regulation No. 55/2019. Many OEM brands have started developing their products and selling their Electric Vehicles. PT. LIS, an Indonesian automobile firm responsible for R and D “LIS” brand in Indonesia, likewise looks to capitalize on this opportunity. However, based on 2019-2021 sales data, “LIS” brand electric vehicle market share is only 0.3% of total EV market. This research discusses the development of new product battery-electric vehicle. It aims to identify what attributes Indonesian consumers consider and combinations of attributes that need to be analyzed into the main preferences of consumers. This research aims to increase value-added and competitiveness of “LIS” brand product innovation towards electric vehicles. A Choice-Based conjoint survey was conducted using the Potentially All Pairwise Rankings of all possible alternatives (PAPRIKA) method using 1000minds software to determine preference weights representing the relative importance of six Battery Electric Vehicle attributes. Cluster analysis was performed to identify clusters of participants with similar importance levels. ANOVA was used to assess differences in individual characteristics by segment. The research sample included 313 participants, 52.1% female, 60.4% 25-40 years old, living in Indonesia. Indonesian consumers’ dominant factors in preference when purchasing battery electric vehicles are reliability and safety rating (23.0%). Furthermore, the other attributes are purchasing price (21.0%), vehicle model (18.3%), charging time (15.1%), driving range (13.6%), and the last is the maximum speed (8.9%). Three clusters or segments were identified: First is the price-sensitive segment, with 142 members or 45.4% of total participants. The second is the premium segment, with 101 members or 32.3% of participants. Last is the value-seeker segment, with 70 members or 22.3% of total participants.